Bifunctional Primary Amine‐Squaramide Catalyzed Enantioselective Intramolecular Michael Addition of Keto‐enones: A Convenient Process to the Stereocontrolled Construction of trans‐Dihydrobenzofuran Skeletons. Issue 22 (17th June 2013) - Liu, Yunting; Lu, Aidang; Hu, Keling; Wang, Youming; Song, Haibin; Zhou, Zhenghong; Tang, Chuchi
Abstract: A highly diasterero‐ and enantioselective intramolecular Michael addition of keto‐enones has been realized. By using the ( R, R )‐1, 2‐diphenylethane‐1, 2‐diamine‐based bifunctional primary amine‐squaramide catalyst, the reaction proceeded smoothly to generate the corresponding trans ‐2, 3‐disubstituted dihydrobenzofuran derivatives in excellent yields with good to excellent diastereo‐ and enantioselectivities (up to 97:3 dr, up to >99 % ee ). Abstract : Optically active trans ‐2, 3‐disubstituted dihydrobenzofurans have been synthesized in excellent yield with good to excellent diastereo‐ and enantioselectivities (up to 97:3 dr, up to >99 % ee ) through a bifunctional primary amine‐squaramide catalyzed intramolecular Michael addition of keto‐enones.